A NEW FRAMEWORK FOR CLASSIFICATION AND QUANTIFICATION OF GEOTHERMAL DIRECT USE RESOURCES AND RESERVES IN INDONESIA: KERANGKA KERJA BARU UNTUK KLASIFIKASI DAN KUANTIFIKASI SUMBER DAYA DAN CADANGAN PEMANFAATAN LANGSUNG PANAS BUMI DI INDONESIA - Husin Setia Nugraha; Rina Wahyuningsih; Dudi Hermawan; Dikdik Risdianto; Husin (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2025)
Geothermal direct use (GDU) in Indonesia holds significant potential for supporting energy security and local economic development, yet its growth has been hindered by the absence of technical standards for potential assessment. In contrast to the well-established indirect use for electricity generation, officially recorded GDU potential remains minimal. This study aims to establish and apply a standardized framework for the classification and quantification of GDU potential and utilization in Indonesia. The developed methodology introduces a potential classification system based on two primary criteria: the quality of fluid data/information and the results of a reserve feasibility study. The potential is categorized into two main classes: Resources (Indicated, Measured) and Reserves (Probable, Proven). Quantification formulas for potential (in MWt) and utilization (installed capacity, capacity factor, annual utilization, and capacity-to-reserve ratio) are also formulated. The initial implementation of this methodology reveals that Indonesia possesses a GDU potential of at least 230 MWt from 201 inventoried prospects, which constitutes approximately 56% of all identified prospects. Of this amount, approximately 8.1 MWt has been successfully classified as Proven Reserves. This standardized framework is expected to serve as a credible national reference for resource inventory, development planning, and attracting investment in the geothermal direct use sector.